ANALYSIS OF FACTORS AFFECTING FARMERS ACCEPTANCE OF RUBBER WAREHOUSE RECEIPT SYSTEM - CHASBIANSARI (NIM 23411041); Pembimbing: Dr. Tota Simatupang, DYAS
Rubber has been stated as a commodity that can be stored in the Warehouse Receipt System (WRS) by BAPPEBTI since 2007. However, the implementation of rubber WRS has not yet been done and it will be started in 2013 to 2014 by making a study of rubber as a subject of WRS. To make the implementation of rubber WRS can be successful, it is necessary to know what WRS factors are influential in the farmers acceptance of rubber WRS. These factors can be used to design an implementation strategy to the successfull implementation of rubber WRS. The aim of this study is to determine the WRS factors that influence the farmers acceptance of rubber WRS. Samples were selected by purposive sampling method. The respondents of this study are rubber farmers who have their own land and produce smoked rubber sheet. Analysis was conducted using component-based Structural Equation Modeling (SEM) approach and SmartPLS 2.0 application. Data gathered using questionnaires from 193 rubber farmers in Banyumas and Cilacap area were collected and analysed using the above method. Results showed that financial procedures and performance procedures affect the farmers acceptance; costs, prices, and banking regulations affect financial procedures; benefits affect the performance procedures; warehouse facility affect the storage procedures. While storage procedures was not proven to affect the farmers acceptance; ability of farmers and environmental support had no affect on storage procedures; process simplicity and governmental support did not prove to affect the performance procedures. Results of this study can be used for implementing rubber WRS, such as, using a pilot project. The pilot project of implementation rubber WRS should be successful, so the farmers would be interested in using rubber WRS. Keywords: warehouse receipt system